Spatial multiplexing for photon-counting MIMO-FSO communication systems - Abou-Rjeily, Chadi (2018)
In this paper, we consider the problem of multiple-input multiple-output (MIMO) free-space optical communications under the Poisson photon-counting detection model. Aiming for high bit rate objectives, we consider the spatial-multiplexing (SMux) solution with M-ary pulse-position modulation, where we propose appropriate optimal and suboptimal decoders and evaluate their complexities. Such novel decoder designs are needed, since the widely spread Gaussian noise-based MIMO decoders are not suitable for the Poisson model. We also carry out an asymptotic performance analysis. This analysis guides a candidate constellation confinement where transmissions are limited to some selected information vectors of the multidimensional SMux constellation. This confinement meets the objective of compromising the multiplexing gains for the sake of improved error-rates. The analyzed SMux solutions with both the unconfined and confined constellations transmit at higher data rates compared with the existing single-aperture systems, MIMO systems with repetition coding, and MIMO systems based on spatial modulation.